Practising Pluriversalism in Africa - Raoul Bunskoek; Maria Ketzmerick-Calandrino (Africa Spectrum)
This special section examines how African and non-African actors, including Chinese and Western, co-produce knowledge through pluralistic encounters. Emphasizing pluriversalism, it challenges Eurocentric universalism and highlights diverse epistemologies and agency. Drawing on case studies from Rwanda, Ghana, and Kenya, it contributes to decolonizing knowledge and advancing post-Western International Relations theory.